Understanding the motivations and implications of climate emergency declarations in cities: The case of Italy. (May 2023) - Salvia, Monica; Reckien, Diana; Geneletti, Davide; Pietrapertosa, Filomena; D'Alonzo, Valentina; De Gregorio Hurtado, Sonia; Chatterjee, Souran; Bai, Xuemei; Ürge-Vorsatz, Diana
Abstract: This study investigates the climate emergency declaration (CED) movement in cities and its effects and synergies with local climate planning. Urban areas are experiencing a wide range of climate-induced extreme events, particularly those located in the Mediterranean hotspot. The focus is on Italian cities, which have only recently become key players in climate planning. The method is based on the collection, analysis, and comparison of data on CEDs and local climate plans (LCPs), integrated with information on city membership in climate networks, to extrapolate key performance indicators of the CED movement. The results show that the CED movement can motivate municipalities to become more ambitious in climate action. As of February 2021, the "climate emergency" movement was supported by 105 Italian cities geographically concentrated in the northern regions (66.7%). The motivation behind a CED is often attributable to local populations calling for concrete climate action (91.1% referred to the Fridays for Future movement) but also to a greater perception of the impacts of climate change (85.6% referred to the Special Report on Global Warming of 1.5 °C). Networking plays an important role (85 cities in the Covenant of Mayors). Interestingly, 36 cities (34.3%) were not engaged in local climate planning previously, but the CED shows now they see the urgency to act. 24.4% cities aim at carbon neutrality in their CEDs (most with local adaptation aspirations), with a much smaller fraction of cities doing so in LCPs and generally lower ambition in terms of greenhouse gas emission reduction targets. Graphical abstract: Image 1 Highlights: Case study: 105 IT cities that have declared climate emergency (66.7% in the north). Motivation: 91.1% refer to the FFF movement, 85.6% to the 2018 IPCC Special Report. Networking: 85 cities are members of CoM and 33 of the Italian Green City Network. 34.3% of the CED cities had not previously a mitigation or adaptation plan. 24.4% of CEDs aim at carbon neutrality, while LCPs have less ambitious GHG targets.